ANALISIS KEBIJAKAN MASALAH PENGANGGURAN SARJANA DI INDONESIA - Hendrikus Triwibawanto Gedeona (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Educated unemployment has become an immense problem in Indonesia in addition to corruption, poverty, and terrorism. This problem arises due to the mismatch between graduate quality and job market necessity. Therefore, government andhigher education institutions should strive for generating highly competent graduates. The writer tries to analyze the problem and recommend alternative solutions to be considered in the policy making to overcome the problem.